Implementing Merdeka Curriculum by Strengthening Character Education (Literature Review): Implementasi Kurikulum Merdeka melalui Penguatan Pendidikan Karakter (Tinjauan Literatur) - Nurmala, Eka; Sabaruddin; Sultan; Hartati, Diah Vitaloka; Siregar, Muhammad Sapril (PT. Alpha Trianguli Australis, 2024)
As technology and science continue to advance rapidly, it is necessary to update the curriculum and learning methods constantly. This helps to meet the demands of the times and the ever-evolving landscape of science and technology. In Indonesia, the government has implemented an independent curriculum to strengthen character education. A Systematic Literature Review (SLR) method was used to research and obtain objective and reliable results. The research showed that educational institutions at all levels have implemented the independent curriculum to support national education goals.